Development of a dynamic model to determine the impact of air pollutant factors in the population of Lima - Rivera Poma, Juan Manuel (2012)
The atmosphere is a major element in the preservation of the quality of life we want. The population growth is one of the main factors that influence air pollution, for what is considered necessary to analyze the relationship of pollution and its effects on the population. The effect of these parameters on pollution and population health has been studied as a cause and effect so that using a computer simulation program; we can study their behavior in the future. In this way we would be in the potential for reducing air pollution, or at least prevent its increase, by control of these parameters.